Systematic review on the benefit of graduated compression stockings in the prevention of venous thromboembolism in low-risk surgical patients. (April 2021) - Machin, M; Younan, HC; Smith, S; Salim, Safa; Davies, AH; Shalhoub, J
Objectives: The aim of this systematic review is to assess the performance of graduated compression stockings (GCS) in comparison to no venous thromboembolism (VTE) prophylaxis in the prevention of hospital-acquired thrombosis in low-risk surgical patients undergoing short-stay procedures. Methods: Aligning with PRISMA guidelines, online databases MEDLINE and EMBASE, Cochrane Library® and trial registries were searched. Eligible articles reported the VTE rate in low-risk surgical patients either receiving GCS or no VTE prophylaxis. Results: Narrative synthesis was performed on a single eligible article. The included study arm consisted of participants undergoing knee arthroscopy with the use of GCS alone reporting a total of 29 VTE events (4.4%), 16 of which were asymptomatic DVTs (2.4%). Conclusion: There is a complete lack of evidence to support the use of GCS in the prevention of HAT for low-risk surgical patients. An adequately powered trial is required to provide level-IA evidence to support this practice.